#### Answer

14

#### Work Step by Step

We first create a common denominator. Then, we use the distributive property to simplify:
$18(\frac{2}{3}+\frac{1}{9})$
=$18(\frac{2(3)+1(1)}{9})$
=$18(\frac{6+1}{9})$
=$18(\frac{7}{9})$
=$2(\frac{7}{1})$
=$14$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

14

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.